High Performance and Active Sites of a Ceria‐Supported Palladium Catalyst for Solvent‐Free Chemoselective Hydrogenation of Nitroarenes. Issue 19 (10th August 2017) - Shi, Xiuxiu; Wang, Xueguang; Shang, Xingfu; Zou, Xiujing; Ding, Weizhong; Lu, Xionggang
Abstract: Cerium oxide‐supported palladium catalysts (Pd/CeO2 ) prepared by a simple impregnation method exhibit exciting catalytic activity and high chemoselectivity for the solvent‐free hydrogenation of a variety of substituted nitroarenes including the reducible functional groups to the corresponding aromatic amines under mild reaction conditions. Taking nitrobenzene as an example, the Pd/CeO2 catalyst can afford aniline yields of >99 % with turnover frequencies as high as 11 411 h −1 and 69 824 h −1 at 40 °C and 100 °C, respectively. Pd 2+ ion species exist as isolated single atoms with −Pd 2+ −O 2− −Ce 4+ − linkages on the surface of Pd x Ce1− x O2− σ solid solution and are found to be active sites for the selective hydrogenation of nitroarenes in the absence of solvent. The superior catalytic performance can be attributed to the cooperative effect between Pd 2+ ions and unique surface sites of CeO2 . A possible mechanism is proposed for the hydrogenation of nitroarenes with H2 over the Pd/CeO2 . The Pd/CeO2 catalyst can be recovered easily and reused for at least seven recycling reactions without loss of catalytic properties. Abstract : Solvent‐free hydrogenation : Cerium oxide‐supported palladium catalysts exhibit exciting catalytic activity and high chemoselectivity for solvent‐free hydrogenation of a variety of substituted nitroarenes under mild reaction conditions. Pd 2+ ions on the surface of Pd x Ce1− x O2− σ solid solutions are found to be the active sites. The superior catalytic performance can be attributed to the cooperative effect between the Pd 2+ ions and unique surface sites of CeO2 .